O emprego das forças armadas em atividades subsidiárias: o caso da Marinha do Brasil - Soares, Renata Cristina Ferreira (2015)
From the democratization, the military began to exercise unusual activity to their primary function of external defense. This study analyzed the case of the Brazilian Navy, and assess the impact of the assumption of subsidiary functions to the Force. For this, we collected data of resources provisioned to the Navy, to finance such activities, and about quantitative personnel and means of naval force reserved to fulfill such missions. Budget data were collected by consulting the Sistema do Plano Diretor, specific computerized system of the Navy. Statistical data were taken from the Anuário Estatístico da Marinha 2013/2014; Memento nº 68 of the Ministério da Defesa; with the Military Organizations; in surveys conducted in intranet sites and at the Naval Force publications. The results show that there was a considerable increase in resources to fund subsidiary activities over the period 2001-2015, more evident from the government of Luiz Inácio Lula da Silva and traversing the mandate of Dilma Rousseff. Nevertheless, they add up to only 2% of the amounts allocated to the Naval Force in 2014, slice that proves to be modest given the mobilization of personnel and operating resources necessary to fulfill such missions. It was concluded that the performance of domestic duties generates negative impacts on the readiness of the forces and compromise the quality of democracy, by encouraging the expansion of military operations in the civil world